The effectiveness of the meta-diagnostic educational package based on cognitive behavioral therapy, schema therapy and meaning therapy on marital conflict of women involved in emotional divorce - Nazemi Zand, Nikta; Ghorban Shiroudi, Shohreh; Khalatbari, Javad; Rahmani, Mohammadali (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of this research was to determine the effectiveness of meta-diagnostic treatment based on cognitive behavioral therapy, schema therapy and meaning therapy on marital conflict of women involved in emotional divorce. Method: The current research method was conducted as a quasi-experimental study with a pre-test-post-test and follow-up design with a control group. The statistical population included all women eligible for emotional divorce in Tehran who referred to the Atiyeh Psychology Clinic in 2018, which was done using available sampling method. Among them, 30 people were randomly selected and replaced in the experimental group, meta-diagnostic training based on cognitive behavioral therapy, schema therapy and meaning therapy (15 people) and the control group (15 people). The educational package developed by the meta-diagnostic researcher based on thematic analysis technique was implemented in ten 90-minute sessions on the experimental group, but the control group remained on the waiting list. The measurement tools used in the research included marital conflicts questionnaire (Barati & Sanai, 1999) and emotional divorce questionnaire (Gottman, 2008). Analysis of variance with repeated measurements and spss software were used to analyze the data. Results: The results indicated that the effect of treatment based on meta-diagnosis of cognitive therapy, schema therapy and meaning therapy in reducing marital conflicts (F=362.36, P<0.001) is effective in follow-up conditions. Conclusion: Therefore, it was concluded that transdiagnostic therapy based on cognitive behavioral therapy, schema therapy and meaning therapy is effective in reducing marital conflicts.